Diagnostics of autoimmune blistering disorders: an experience of a single tertiary referral centre - Adaszewska, Alicja; Woźniak, Katarzyna; Kalińska-Bienias, Agnieszka; Smolarczyk, Katarzyna; Kowalewski, Cezary (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Autoimmune blistering disorders (AIBD) include a heterogeneous group of diseases characterized by the presence of autoantibodies against the structural antigens of the skin and mucous membranes. The gold standard of AIBD diagnostics is the detection of in vivo bound IgG/IgA and/or complement component 3 in the direct immunofluorescence of a perilesional biopsy. Various immunological techniques such as indirect immunofluorescence of different tissue substrates including monkey oesophagus, salt split skin, recombinant proteins of epidermis and basement membrane zone as well as ELISA systems and immunoblotting are used to characterize target antigens. Proper and early diagnosis is crucial for both treatment and prognosis since some AIBD may be associated with a malignant neoplasm.